(untitled) (CIPEEX, 2025)
Trauma is a significant cause of disability, especially when it involves lower limbs, highlighting the importance of managing postoperative pain and the psychological factors associated with recovery. Thus, the objective was to evaluate the occurrence and association between the level of pain and kinesiophobia in patients in the immediate postoperative period after lower limb trauma. A cross-sectional study with quantitative analysis was conducted at a reference orthopedic hospital, following approval by the CEP (No. 6970562), and investigated the relationship between age, sex, pain, and kinesiophobia in 92 volunteer postoperative patients. The Visual Analog Scale for Pain (VAS) and the Tampa Scale for Kinesiophobia were used, revealing that the majority of volunteers presented moderate levels of both kinesiophobia and pain. However, no significant association was found between the factors sex and kinesiophobia (p=0.711), between VAS and the presence of kinesiophobia (p=0.937), nor between VAS and sex (p=0.785). The results indicate the need for further studies to better understand the interaction between psychological factors and post-trauma recovery.